18F-FDG PET/CT compared with ultrasound and biopsy for detection of vasculitis of the temporal artery branches - Christof Rottenburger; Noemi Mensch; Stephan Imfeld; Markus Aschwanden; Katharina Glatz; Daniel Staub; Christoph T. Berger; Thomas Daikeler (Swiss Medical Weekly, 2021)
AIMS